Implied Default Probabilities and Losses Given Default from Option Prices. (21st September 2020) - Conrad, Jennifer; Dittmar, Robert F; Hameed, Allaudeen
Abstract: We propose a novel method of estimating default probabilities using equity options data. The resulting default probabilities are highly correlated with estimates of default probabilities extracted from CDS spreads, which assume constant losses given default. Additionally, the option-implied default probabilities are higher in bad economic times and for firms with poorer credit ratings and financial positions. A simple inferred measure of loss given default is related to underlying business conditions, and varies across sectors; the time series properties of this measure are similar after controlling for liquidity effects.